Small antenna design - Miron, Douglas B. (Communications engineering series., 2006)
As wireless devices and systems get both smaller and more ubiquitous, the demand for effective but small antennas is rapidly increasing. This book will describe the theory behind effective small antenna design and give design techniques and examples for small antennas for different operating frequencies. Design techniques are given for the entire radio spectrum, from a very hundred kilohertz to the gigahertz range. Unlike other antenna books which are heavily mathematical and theoretical, Douglas Miron keeps mathematics to the absolute minimum required to explain design techniques. Ground planes, essential for operation of many antenna designs, are extensively discussed. The book will also include a CD-ROM with design software that will greatly simplify readers' daily design tasks. *Author's extensive experience as a practicing antenna design engineer gives book a strong "hands-on" emphasis *Covers antenna design techniques from very low frequency (below 300 kHz) to microwave (above 1 GHz) ranges *Special attention is given to antenna design for mobile/portable applications such as cell phones, WiFi, etc